A Health Education about Sefl-Prevention of Covid-19 Transmission - Jumaroh Jumaroh; Eka Budiarto (Global Health Science Group, 2022)
Along with the widespread Covid-19 pandemic, limitless information related to the virus, the pandemic, and their impacts spread wildly either. It may cause not only misunderstanding, but also confusion, anxiety, and fear among people. This community service aimed to share the proper and sufficient information about the pandemic based on valid references to raise people awareness, increase their understanding about the pandemic, and to show them ways to differ valid information from the invalid ones. The health education was carried out door-to-door and in informal setting. During the activities the respondents received the printed material, explanation about the material, answers for their questions, and face masks. The activity ran smoothly and the respondents took part actively. Therefore, health care personnel are supposed to spread valid information about the Covid-19 pandemic to wider communities to create better understanding and avoid any misunderstanding among people in general.